2018
DOI: 10.3389/fnins.2018.00889
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Intrinsic Functional Connectivity of the Salience Network in Drug-Naïve Patients With Obsessive-Compulsive Disorder

Abstract: Obsessive-compulsive disorder (OCD) patients have difficulty in switching between obsessive thought and compulsive behavior, which may be related to the dysfunction of the salience network (SN). However, little is known about the changes in intra- and inter- intrinsic functional connectivity (iFC) of the SN in patients with OCD. In this study, we parceled the SN into 19 subregions and investigated iFC changes for each of these subregions in 40 drug-naïve patients with OCD and 40 healthy controls (HCs) using se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Diverse studies typically generate inconsistent results (2). Furthermore, some studies have focused on the networks of interest and ignored the most crucial brain areas involved in the core pathological abnormalities in OCD (12,13,15,(28)(29)(30). By contrast, in the present research, we used a voxel-wise brain-wide method to focus on FC alterations in drug-naive patients with OCD at rest.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Diverse studies typically generate inconsistent results (2). Furthermore, some studies have focused on the networks of interest and ignored the most crucial brain areas involved in the core pathological abnormalities in OCD (12,13,15,(28)(29)(30). By contrast, in the present research, we used a voxel-wise brain-wide method to focus on FC alterations in drug-naive patients with OCD at rest.…”
Section: Discussionmentioning
confidence: 90%
“…As an important member in the triple network model, the SN filters and detects the external and internal salient information, and has an important role in supervising the interactions between the DMN and ECN (8). In our previous study, decreased FC strength within the SN, between the SN and ECN, and the DMN in OCD at rest was revealed (15). In that study, we only focused on the SN and ignored other important brain regions involved in OCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous static rfMRI studies in patients with OCD found decreased FC between DMN and SAN and other task‐positive networks (Chen et al, 2018; Cyr et al, 2020), and a meta‐analysis of static FC studies found hypoconnectivity among FPN, SAN, and DMN (Gursel et al, 2018). The present findings suggest that a higher occurrence of a state with the lowest FC between networks might be the neural substrate for the decreased static FC between DMN and SAN in OCD.…”
Section: Discussionmentioning
confidence: 94%
“…Apart from structural abnormalities, functional studies also highlight the importance of trans‐callosal connectivity alterations in OCD. Adult patients with OCD have been reported to have decreased functional connectivity between the right ventral lateral prefrontal cortex and left insula (Chen et al., 2018) and decreased voxel‐mirrored homotopic connectivity in the precentral gyrus and orbitofrontal cortex (Deng et al., 2019). Additionally, increased functional frontal asymmetry in patients with OCD has been observed in electroencephalography studies (Perera et al., 2019).…”
Section: Discussionmentioning
confidence: 99%